Oral contraception and menstrual bleeding during treatment of venous thromboembolism: expert opinion versus current practice : combined results of a systematic review, expert panel opinion and an international survey - Klok, Erik; Schreiber, Karen; Stach-Jablonski, Ksenija (Thrombosis research, 2017)
Introduction: The optimal management of oral contraception and menstrual bleeding during treatment of venous thromboembolism (VTE) is largely unknown. We aimed to elicit expert opinion and compare that to current practice as assessed by a world-wide international web-based survey among physicians. Methods: 10 international thrombosis experts and 10 abnormal uterine bleeding experts independently completed a questionnaire containing three hypothetical patient cases each with four different scenarios, and additional queries covering different severities of VTE, patient circumstances, hormonal contraceptives and both thrombotic and bleeding complications. The consensus percentage was set a priori at ≥70%. The same questionnaire with randomized case scenarios was presented to international physicians via newsletters of the ISTH and national scientific communities. Differences between the expert groups and daily clinical care were assessed. Results: Expert recommendations were divergent and differed in several important points from clinical practice. In contrast to common practice in which contraceptives are discontinued at the moment of a VTE diagnosis, the thrombosis experts agreed to continue oral contraception (OC) during the anticoagulation treatment period. Also, experts reached consensus on treating patients with anticoagulation-associated abnormal uterine bleeding with tranexamic acid, although this is not supported by strong evidence from the literature. No consensus was reached on the optimal anticoagulant drug class. Conclusions: International experts' opinions on handling of contraceptives and management of anticoagulant-associated abnormal uterine bleeding in female VTE patients are divergent and management in clinical practice is heterogeneous. There is a great need of further studies on these topics.
Available online 20 March 2017
Gesehen am 25.09.2018